CRP-Induced NLRP3 Inflammasome Activation Increases LDL Transcytosis Across Endothelial Cells - Bian, Fang; Yang, Xiao-Yan; Xu, Gao; Zheng, Tao; Jin, Si (Frontiers in Pharmacology, 2019)
NLRP3 inflammasome, a multiprotein cytosolic complex that activates the IL-1 family of cytokines, plays an important role in atherosclerosis (AS). High-sensitivity c-reactive protein (hs-CRP) is widely recognized as a major cardiovascular risk predictor and recent studies name NLRP3 as a predictor of CRP levels. Mounting evidence has indicated that subendothelial retention of apolipoprotein B100-containing lipoproteins, such as low-density lipoprotein (LDL), is the initial step of atherogenesis, and is usually termed the ‘response to retention hypothesis’. We previously reported that CRP promotes AS by directly increasing LDL transcytosis across endothelial cells (ECs). The present study aims to investigate the effects of CRP on NLRP3 inflammasome activation and the roles of NLRP3 inflammasome in CRP-induced LDL transcytosis. We found that CRP enabled to upregulate NF-κB activity, while NF-κB inhibitor (BAY-11-7082) and Fcγ receptors (FcγRs) inhibitor (CD32/64Ab) blocked CRP-induced NF-κB activation. Meantime, CRP induced the expression of pro-IL-1β and NLRP3, while BAY and CD32/64 Ab suppressed CRP-mediated NLRP3 and pro-IL-1β expressions. Moreover, CRP activated NLRP3 inflammasome in ECs. NADPH oxidase inhibitor, diphenylene iodonium (DPI) and dithiothreitol (DTT), a broad-spectrum P2 receptor inhibitor, oxidized ATP (oATP), and a broad inhibitor of cysteine proteases, E-64d, inhibited CRP-induced NLRP3 inflammasome activation. Furthermore, NLRP3 siRNA and caspase-1 inhibitor could block CRP-mediated LDL transcytosis across ECs. In conclusion, NLRP3 activation were involved in CRP-mediated LDL transcytosis across ECs. CRP not only increased the expression of pro-IL-1β and NLRP3 via the FcγRs/NF-κB pathway, but also promoted NLRP3 inflammasome activation and IL-1β maturation by upregulation of reactive oxygen species (ROS) levels, purinergic receptor signaling, and cysteine proteases activity.